2021
DOI: 10.1016/j.dib.2021.107315
|View full text |Cite
|
Sign up to set email alerts
|

Safety-factor dataset for high embankments determined with different analytical methods

Abstract: Slope-stability analysis is one of the parameters in the design of road embankments that the designer must consider in order to ensure stable and safe construction. The technical standards recommend slopes to heights of 12 m, depending on the soil types and the topography. In the present work, the limit equilibrium methods (Fellenius, Bishop, Janbu, Morgensten-Price) and the finite element method are used to determine the safety factor of road embankments for different slopes flanking the road. Five embankment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Besides, the geo-bag method showed the factor of safety with 3.7 which is slightly lower than model with geotextile which had the value of 3.8. It can be seen that all methods meet the minimum requirement for safety factor, where any values that are greater than 1.5 are acceptable safety factors [6]. This section concluded that as the settlement of the embankment had been increased, the factor of safety value has gone down [7].…”
Section: Factor Of Safetymentioning
confidence: 94%
“…Besides, the geo-bag method showed the factor of safety with 3.7 which is slightly lower than model with geotextile which had the value of 3.8. It can be seen that all methods meet the minimum requirement for safety factor, where any values that are greater than 1.5 are acceptable safety factors [6]. This section concluded that as the settlement of the embankment had been increased, the factor of safety value has gone down [7].…”
Section: Factor Of Safetymentioning
confidence: 94%
“…The data has been obtained from an open-source repository for this study (Mesa-Lavista et al. , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The data has been obtained from an open-source repository for this study (Mesa-Lavista et al, 2021). This dataset will be utilized for training and testing the machine learning models.…”
Section: Utilized Databasementioning
confidence: 99%
“…The data obtained for this research were from an open-source repository [35]. The dataset that will be in this study used for training and testing the ANN models were collected from comprehensive parametric research on various road embankments' safety factors computed using the finite element approach.…”
Section: Utilized Databasementioning
confidence: 99%